Management of Alternaria leaf blight of Mateera (watermelon) by fungicides, bio-agents and botanical (Indian Journal of Arid Horticulture, 2025)
The field trials were conducted for management of Alternaria leaf blight (Alternaria cucumerina var. P. watermelon) in mateera (watermelon) by fungicides, bio-agents and botanical during summer season of 2013 and 2014 at Plant Pathology Block of ICAR-Central Institute for Arid Horticulture, Bikaner (Rajasthan). Three fungicides (copper oxychloride, carbendazim and mancozeb), four bio-agents (Aspergillus niger, Pseudomonas fluorescens CIAH-196, Trichoderma viride CIAH-240 and Trichoderma viride Non-Resistant) and one botanical such as onion leaf extract were taken for the study. Disease incidence and disease severity of Alternaria leaf blight in mateera ranged from 10.0 to 34.17% and 8.88 to 29.01%, respectively. Among nine treatments, one foliar spray of mancozeb (0.25%) proved the most effective fungicide for the management of this disease in mateera under field conditions with the minimum disease incidence (10.0%) and disease severity (8.88%) and the maximum disease control (69.39%). Further, next best treatment was Trichoderma viride CIAH-240 (5%). However, the maximum disease incidence (34.17%) and disease severity (29.01%) were observed in control followed by onion leaf extract (5%) with disease incidence (27.85%), disease severity (24.34%) and the minimum disease reduction (16.09%).
Keywords: Alternaria leaf blight; mateera (watermelon); bio-agents; botanical; fungicides; management